A novel method for quality consistency evaluation of Glycyrrhiza formula granules based on a spectrum‐effect study. Issue 2 (22nd November 2022) - Zhou, Yongfeng; Wang, Junnan; Tan, Peng; Wu, Qinghua; Chen, Jiang; Liu, Jiaxin; Zhang, Ping; Zhang, Dingkun; Pei, Jin
Abstract : Quality consistency of Glycyrrhiza formula granules is essential for guaranteeing clinical efficacy. However, a suitable method to accurately and conveniently evaluate the consistency of the clinical efficacy of Glycyrrhiza formula granules is currently not available. This study established a method for the simultaneous determination of 12 active components in Glycyrrhiza formula granules using ultra‐high‐performance liquid chromatography coupled with quadrupole‐time‐of‐flight tandem mass spectrometry. The rate of inhibition of cyclooxygenase‐2 by different batches of Glycyrrhiza formula granules was determined. Near‐infrared spectra were collected for different batches of Glycyrrhiza formula granules to detect their biological activity in the inhibition of cyclooxygenase‐2. The quality consistency of the 11 batches of Glycyrrhiza formula granules was evaluated using principal component and correlation analyses. The results showed significant differences in the formula granules of Glycyrrhiza uralensis produced by the different manufacturers. Some differences were also observed among batches of formula granules produced by the same manufacturer. Correlation analysis of the chemical components and cyclooxygenase‐2 activity showed that glycyrrhizic acid, liquiritin, and isoliquiritin were the main active components of Glycyrrhiza . Correlation analysis of the near‐infrared spectra and cyclooxygenase‐2 inhibition activity showed a high correlation between the active components and three characteristic bands: 3383–3995, 4227–4651, and 5315–5878 cm −1 . In this study, the main active anti‐inflammatory components of Glycyrrhiza granules were screened. Thus, the near‐infrared spectrum and characteristic active band of multi‐index active components can be used to quickly detect the quality consistency of Glycyrrhiza formula granules, thereby improving the ability to control the quality and consistency of these granules.